2012
DOI: 10.1002/hyp.9601
|View full text |Cite
|
Sign up to set email alerts
|

Influence of partial confinement and Holocene river formation on groundwater flow and dissolution in the Florida carbonate platform

Abstract: Abstract:Much of what is known about groundwater circulation and geochemical evolution in carbonate platforms is based on platforms that are fully confined or unconfined. Much less is known about groundwater flow paths and geochemical evolution in partially confined platforms, particularly those supporting surface water. In north-central Florida, sea level rise and a transition to a wetter climate during the Holocene formed rivers in unconfined portions of the Florida carbonate platform. Focusing on data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Though a few site-specific studies have examined controls on carbonate system dynamics using time series data [e.g., Liu et al, 2004;Groves and Meiman, 2005;Pu et al, 2014], more work is needed to fully understand what determines whether dilution or CO 2 is important in a given setting or under given conditions. Prior work has shown that dilution is an important control on dissolution where runoff from noncarbonate rocks, which is undersaturated, mixes with or displaces groundwater from carbonate aquifers, which is saturated [Gulley et al, 2013[Gulley et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though a few site-specific studies have examined controls on carbonate system dynamics using time series data [e.g., Liu et al, 2004;Groves and Meiman, 2005;Pu et al, 2014], more work is needed to fully understand what determines whether dilution or CO 2 is important in a given setting or under given conditions. Prior work has shown that dilution is an important control on dissolution where runoff from noncarbonate rocks, which is undersaturated, mixes with or displaces groundwater from carbonate aquifers, which is saturated [Gulley et al, 2013[Gulley et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Dilute samples with high dissolved organic matter concentrations can produce substantial charge balance errors because dissolved organic carbon interferes with titrations and contributes to charge balance [Hemond, 1990]. Therefore, uncertainty in dissolution rates was assessed by alternately forcing charge balance on calcium and alkalinity [Gulley et al, 2013[Gulley et al, , 2014. Error bars depict dissolution rates calculated using this alternate charge balance forcing.…”
Section: Processing Of Water Chemistry Datamentioning
confidence: 99%
“…The lithology for type T-L is limestone, which is easily dissolved by water, resulting in a thin layer of soil and small bulk density. The lithology for the M type is dolomite; dolomite and argillaceous limestone usually form a semi-karst landscape that differs from the karst [33,34]. Dolomite belongs to carbonate rocks, which can retain a part of the weathering products, forming a soil thickness and bulk density between those of the former two types.…”
Section: Influence Of Topsoil Conditions On Surface Runoffmentioning
confidence: 99%
“…Sink‐rise systems are enlarged by runoff from low permeability non‐carbonate bedrock, which is typically undersaturated with respect to carbonate minerals, particularly during floods (Palmer, ). Attenuation of flood peaks can be substantial in sink‐rise systems because large volumes of water can be stored in conduit porosity when caves are air‐filled (Dogwiler and Wicks, ; Covington et al ., ) and in the surrounding aquifer matrix when hydraulic head differences between conduit and matrix force floodwaters into the surrounding aquifer (Martin and Dean, ; Screaton et al ., ; Gulley et al, ). For example, transient aquifer storage in a prominent sink‐rise system in a karstic watershed in north‐central Florida reduced peak discharge by 40%, relative to upstream gaging stations during flooding associated with a tropical storm (Gulley et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Transient aquifer storage, defined herein as the temporary loss of river water to aquifers during floods and subsequent return to the river, has been recognized in contributing to flood peak attenuation (Cooper Jr and Rorabaugh, 1963;Zitta and Wiggert, 1971;Pinder and Saurer, 1971;Moench and Barlow, 2000;Chen and Chen, 2003). Transient aquifer storage typically occurs in watersheds that cross hydraulic boundaries, where upstream portions of the watershed are underlain by lowpermeability substrate and downstream portions of the watershed are underlain by substrate with higher permeability (Bonnaci, 1996;Gulley et al, 2013Gulley et al, , 2014. Examples include basins where rivers flow off low permeability crystalline rocks onto adjacent alluvial aquifers (Winter, 1999;Sophocleous, 2005;Payn et al, 2009), glacial terrain (Winter and Pfannkuch, 1976), volcanic terrain (Konrad, 2006) and dryland rivers in semi-arid regions (Costa et al, 1992).…”
Section: Introductionmentioning
confidence: 99%